Human Rights and Legal Protection for Victims of Arrest by Police in Indonesia - Dijan Widijowati (Research Horizon, 2023)
The Indonesian National Police (Polri) plays a crucial role in upholding security and public order as a law enforcement agency, directly engaging with civil society and carrying out various law enforcement tasks in Indonesia, including investigations. Nevertheless, incidents of wrongful arrests by the Police persist, indicating investigators' actions lacking a clear basis and leading to arbitrary arrests without due consideration. Such flawed investigations can result in serious issues, violating the rights of wrongly arrested individuals and undermining public trust in the police and the justice system. This study adopts a normative juridical approach, drawing on legal principles, relevant laws, regulations, and literature to examine human rights and legal protection for victims of wrongful arrests by the police in Indonesia. The analysis highlights the urgent need to bolster human rights protection in law enforcement. To address this, greater efforts are required to enhance police officers' understanding and awareness of human rights and legal safeguards for victims of wrongful arrests. Moreover, providing legal redress for victims can be accomplished through compensation and rehabilitation mechanisms, aiming to reinstate violated rights and improve victims' situations. Implementing such mechanisms offers hope for victims to attain proper justice and remedies, while also preventing similar errors in the future and increasing the accountability of law enforcement officials.